2010
DOI: 10.1051/epjconf/20100603002
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent behaviour of high performance concrete: influence of coarse aggregate characteristics

Abstract: Abstract. This paper examines the influence of coarse aggregate characteristics on the time-dependent deformations of High Performances Concretes (HPC). Four concretes made using the same cement paste but incorporating different types of aggregate (rolled siliceous gravel, crushed granite, crushed limestone and crushed siliceous gravels) were studied in order to investigate the effect of aggregate properties on the compressive strength, modulus of elasticity, shrinkage and creep. The results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…Poon et al 62 stated that the compressive strength would be better when granite aggregate was used in place of recycled aggregate. Makani et al 63 reported that using limestone aggregate as coarse aggregate in place of granite or siliceous coarse aggregate would give better results. Echeta et al 64 reported that a mixture prepared with 80% washed gravel and 20% granite aggregate gave the highest increase in compressive strength (53.9%).…”
Section: Substitution Of Coarse Aggregates With Crushed Granitementioning
confidence: 99%
See 1 more Smart Citation
“…Poon et al 62 stated that the compressive strength would be better when granite aggregate was used in place of recycled aggregate. Makani et al 63 reported that using limestone aggregate as coarse aggregate in place of granite or siliceous coarse aggregate would give better results. Echeta et al 64 reported that a mixture prepared with 80% washed gravel and 20% granite aggregate gave the highest increase in compressive strength (53.9%).…”
Section: Substitution Of Coarse Aggregates With Crushed Granitementioning
confidence: 99%
“…Makani et al 63 The effect of coarse aggregate type on the mechanical properties of high-strength concrete (HPC)…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Again, longer periods of time are required for the application to bridges. The influence of the type of aggregate has also been studied in laboratory tests …”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of the type of aggregate has also been studied in laboratory tests. 9 In terms of the long-term behavior of high-strength prestressed concrete box girder bridges, limited information is available, none of which was available at the time of design of the Second Stichtse Bridge. In China, the long-term behavior of a segmental concrete cantilever T-beam of 12.8 m in length has been studied 10 to simulate the construction process of the Sutong Bridge.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Elastik modulus konkrit juga dipengaruhi oleh bentuk dan tekstur agregat. Kajian oleh Makani et al (2010) telah mendapati bahawa konkrit campuran agregat berbentuk ellipsoid mempunyai elastik modulus yang lebih tinggi berbanding dengan agregat berbentuk bulat. Selain itu, zon peralihan antara muka (ITZ) berlaku pada konkrit juga berbeza semasa dibawa beban yang berlainan.…”
unclassified